2018
DOI: 10.26582/k.50.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Achievement goals and self-determination in adult football players – a cluster analysis

Abstract: Abstract:To better understand the relationship between aspects of motivation and performance level in adult football players, this study aimed to identify differences in motivation among different motivational profiles created by means of hierarchical cluster analysis. The participants were 304 adult football players (90 professionals, 144 semi-professionals, 70 amateurs, age: 25.4±4.6 years). Participants completed the Task and Ego Orientation in Sports Questionnaire and the Self-Regulation Questionnaire. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Concerning goal orientations, we could see that throughout the season our players are clearly more taskoriented than ego-oriented, focusing their motivation on their level of performance, their ability to overcome and on their own dominance, and not on the comparison and competitiveness with the rest. The Portuguese footballers in the study by Sarmento et al (2018) also showed a clear inclination to task without differences between the categories. These results are corroborated not only by other work of professional Spanish football players (Granero et al, 2015), but also in young male football players (Fernandez et al, 2014), and in professional female athletes in various sports (Fernandez-Rio et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Concerning goal orientations, we could see that throughout the season our players are clearly more taskoriented than ego-oriented, focusing their motivation on their level of performance, their ability to overcome and on their own dominance, and not on the comparison and competitiveness with the rest. The Portuguese footballers in the study by Sarmento et al (2018) also showed a clear inclination to task without differences between the categories. These results are corroborated not only by other work of professional Spanish football players (Granero et al, 2015), but also in young male football players (Fernandez et al, 2014), and in professional female athletes in various sports (Fernandez-Rio et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, when comparing the results of this scale by categories, there are no differences found, showing a quite similar profile with a high intrinsic component. Neither Sarmento et al (2018), found differences in the self-determined motivation among the Portuguese male football categories, showing also a high intrinsic component.…”
Section: Discussionmentioning
confidence: 77%
“…Remember that this motivational climate improves the relationship between the athlete and the trainer [ 55 ], increases motivational self-discipline in the athlete [ 56 ], boosts the belief in their own ability, and raises the intention of being physically active in the future [ 57 ], as well as different over-arching aspects like physical effort [ 23 ]. It is worth pointing out that other studies carried out on top level sports-women have demonstrated that females are more highly orientated towards the task in sports such as basketball [ 31 ] and football [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…While using the k-means clustering method is nothing new for sports, a detailed literature review search found noth-ing specific to its application in American football for the purposes of identification of training groupings. Soccer, on the other hand, has had a number of recent studies utilizing k-means clustering for everything from pregame expectations of the athlete (Popovych et al, 2020), to special movement patterns during a game (Beernaerts, de Baets, Lenoir, & van de Weghe, 2020), to game performance as it relates to new contracts (Gómez, Lago, Gómez, & Furley, 2019), to self-determination (Sarmento, Peralta, Harper, Vaz, & Marques, 2018) and emotional intelligence (Louvet & Campo, 2020), to the risk of eating disorders (Izquierdo, Ceballos, Ramírez Molina, Vallejo, & Díaz, 2019). One soccer study did find that k-means clustering was not a good technique for assessing the four velocity zones during a match because of the subtle differences between velocity thresholds based on the Catapult Sports MinimaxX S4 TM used (Park, Scott, & Lovell, 2019).…”
Section: Seasonmentioning
confidence: 99%